Relaxant Effects of the Selective Estrogen Receptor Modulator, Bazedoxifene, and Estrogen Receptor Agonists in Isolated Rabbit Basilar Artery. Issue 4 (October 2016) - Castelló-Ruiz, María; Salom, Juan B.; Fernández-Musoles, Ricardo; Burguete, María C.; López-Morales, Mikahela A.; Arduini, Alessandro; Jover-Mengual, Teresa; Hervás, David; Torregrosa, Germán; Alborch, Enrique
Abstract : Abstract: We have previously shown that the selective estrogen receptor modulator, bazedoxifene, improves the consequences of ischemic stroke. Now we aimed to characterize the effects and mechanisms of action of bazedoxifene in cerebral arteries. Male rabbit isolated basilar arteries were used for isometric tension recording and quantitative polymerase chain reaction. Bazedoxifene relaxed cerebral arteries, as 17-β-estradiol, 4, 4′, 4″-(4-propyl-[1H]-pyrazole-1, 3, 5-triyl)trisphenol [estrogen receptor (ER) α agonist], and G1 [G protein-coupled ER (GPER) agonist] did it (4, 4′, 4″-(4-propyl-[1H]-pyrazole-1, 3, 5-triyl)trisphenol > bazedoxifene = G1 > 17-β-estradiol). 2, 3-Bis(4-hydroxyphenyl)-propionitrile (ERβ agonist) had no effect. Expression profile of genes encoding for ERα (ESR1), ERβ (ESR2), and GPER was GPER > ESR1 > ESR2. As to the endothelial mechanisms, endothelium removal, N G -nitro-L-arginine methyl ester, and indomethacin, did not modify the relaxant responses to bazedoxifene. As to the K + channels, both a high-K + medium and the Kv blocker, 4-aminopyridine, inhibited the bazedoxifene-induced relaxations, whereas tetraethylammonium (nonselective K + channel blocker), glibenclamide (selective KATP blocker) or iberiotoxin (selective KCa blocker) were without effect. Bazedoxifene also inhibited both Ca 2+ - and Bay K8644-elicited contractions. Therefore, bazedoxifene induces endothelium-independent relaxations of cerebral arteries through (1) activation of GPER and ERα receptors; (2) increase of K + conductance through Kv channels; and (3) inhibition of Ca 2+ entry through L-type Ca 2+ channels. Such a profile is compatible with the beneficial effects of estrogenic compounds (eg, SERMs) on vascular function and, specifically, that concerning the brain. Therefore, bazedoxifene could be useful in the treatment of cerebral disorders in which the cerebrovascular function is compromised (eg, stroke).